Religion, Platonist Dialectics, and Pragmatist Analysis: Marcus Tullius Cicero’s Contributions to the Philosophy and Sociology of Divine and Human Knowing - Prus, Robert (Qualitative Sociology Review, 2021)
Whereas Socrates, Plato, Aristotle and Augustine are probably the best known of the early Western philosophers of religion, Marcus Tullius Cicero (106-43 BCE) also played a particularly consequential role in the development and continuity of Greco-Latin-European social thought. Cicero may be best known for his work on rhetoric and his involvements in the political intrigues of Rome, but Cicero’s comparative examinations of the Greco-Roman philosophies of his day merit much more attention than they have received from contemporary scholars. Cicero’s considerations of philosophy encompass much more than the theological issues considered in this statement, but, in the process of engaging Epicurean and Stoic thought from an Academician (Platonist) perspective, Cicero significantly extends the remarkable insights provided by Socrates, Plato, and Aristotle. Although especially central to the present analysis, Cicero’s On the Nature of the Gods (1972) is only one of several texts that Cicero directs to a comparative (multiparadigmatic and transhistorical) analysis of divine and human knowing. Much of Cicero’s treatment of the philosophy of religion revolves around variants of the Socratic standpoints (i.e., dialectics, theology, moralism) that characterized the philosophies of Cicero’s era (i.e., Stoicism, Epicureanism, Academician dialectics), but Cicero also engages the matters of human knowing and acting in what may be envisioned as more distinctively pragmatist sociological terms. As well, although Cicero’s materials reflect the socio-historical context in which he worked, his detailed analysis of religion represents a valuable source of comparison with present day viewpoints and practices. Likewise, a closer examination of Cicero’s texts indicates that many of the issues of divine and human knowing, with which he explicitly grapples, have maintained an enduring conceptual currency. This paper concludes with a consideration of the relevance of Cicero’s works for a contemporary pragmatist sociological (symbolic interactionist) approach to the more generic study of human knowing and acting.